Microbacterium luticocti sp. nov., isolated from sewage sludge compost - Vaz-Moreira, Ivone (2011)
Strain SC-087BT, isolated from sewage sludge compost during a study of bacterial diversity in composts, was characterized. The isolate was a Gram-positive, short rod that was motile, catalase- and oxidase-negative and able to grow at 27–45 6C, pH 5.5–9.7 and in up to 10% NaCl. The peptidoglycan was of the B2b type, containing the characteristic amino acids ornithine, homoserine and hydroxyglutamic acid. The muramic acid residues of the peptidoglycan were partially glycolylated. The major cell-wall sugar was mannose; traces of xylose were also detected. The predominant fatty acids, comprising more than 70% of the total, were anteiso-C17 : 0 and anteiso-C15 : 0, the major respiratory quinone was menaquinone-12 (MK-12) and the G+C content of the genomic DNA was 72 mol%. Based on analysis of the 16S rRNA gene sequence, the closest phylogenetic neighbours of strain SC-087BT were members of the family Microbacteriaceae, showing sequence similarity values of around 96% with members of the species Microbacterium barkeri (96.0 %), Microbacterium gubbeenense (95.6 %) and Microbacterium indicum (95.7 %). The chemotaxonomic and phenotypic traits analysed supported the inclusion of this strain within the genus Microbacterium and the proposal of a novel species. The name Microbacterium luticocti sp. nov. is proposed and the type strain is SC-087BT (5DSM 19459T5CCUG 54537T).